Imagery Intervention for Developing internal Motivation and Sport Confidence of boxing Players - Solanki, Ajay (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The aim of the present study was to develop internal motivation and sport confidence of boxing players, through imagery intervention. The sample of the study comprised 12 interuniversity level boxing players, between the age ranges of 18 to 24 years. Movement imagery Questionnaire-Revised (Hall etal., 1997) was used to screen out the subjects, on the basis of their imagery ability. Intended motivation was measured through internal Motivation Inventory (Ryan, 1982), and sport confidence was assessed though the Carolina Sprat Confidence Inventory (Manzo, Silva and Mink, 2001). Multivariate Analysis of Variance (MANOVA) was used to analyze the data. The findings revealed that the subjects, in post-intervention condition, scored significantly higher on internal motivation. Sport confidence of the players also increased to significant level. However, the overall F-ratio for multivariate analysis was not found to be significant. Findings of this study provide useful evidence that imagery intervention can be a useful source to develop internal motivation and sport confidence of boxing players, which may further enhance their sport performance.